3-3*2=0

Simple and best practice solution for 3-3*2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-3*2=0 equation:


Simplifying
3 + -3 * 2 = 0

Multiply -3 * 2
3 + -6 = 0

Combine like terms: 3 + -6 = -3
-3 = 0

Solving
-3 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -2f(t+2)= | | 10a-10=6a+2 | | 3(x+5y)+2x+y= | | -17+v=-17 | | 5(2u+3)= | | -13v=156 | | -3(3h+1)= | | 11x+3y=-5 | | 9a-30=78 | | a/30=3/10 | | 7(2a+1)= | | 15x-5y=45 | | x^2+225-289=0 | | 4s-5=-12+5s | | 2c+4-3c=-9+c-5 | | x+13=-29 | | -3(2n-1)= | | 72/x=80/100 | | 7(2a-2)= | | 4.9*0.8= | | 4x-19=209 | | 7-(3y-8)=5-4y | | 8t-22=-30+4t | | 27-5z=-9(4z+3) | | -6(8x-3)=126 | | -3(2k+3)= | | -9(x+2)=2-8x | | 25-4x=10-9x | | 20=5(3b-4) | | 2(8b+2)= | | 42y+4=707 | | 5(k+3)-(-6k-2)=10k |

Equations solver categories